2016
DOI: 10.1016/j.jascer.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and optical properties of CZTS thin films prepared by SILAR method

Abstract: a b s t r a c tIn the present work, Cu 2 ZnSnS 4 (CZTS) thin film was deposited onto the glass substrate by simple and economic SILAR method and its structural, morphological, optical and electrical properties were analyzed Q2 . X-ray diffraction (XRD) analysis confirms the formation of CZTS with kesterite structure and the average crystallite size is found to be 142 nm. Scanning electron microscope (SEM) image shows that the film has homogeneous, agglomerated surface without any cracks. The prepared CZTS film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(45 citation statements)
references
References 27 publications
8
36
0
1
Order By: Relevance
“…Figure 3 shows the optical absorption spectrum of the samples. This data matches with previous measurements in comparative samples [27,28]. In the ultraviolet region, close to 300 nm wavelength can be observed a well-defined peak associated with the SiO 2 substrate absorbance.…”
Section: Nanosecond Third-order Nonlinear Optical Measurementssupporting
confidence: 92%
“…Figure 3 shows the optical absorption spectrum of the samples. This data matches with previous measurements in comparative samples [27,28]. In the ultraviolet region, close to 300 nm wavelength can be observed a well-defined peak associated with the SiO 2 substrate absorbance.…”
Section: Nanosecond Third-order Nonlinear Optical Measurementssupporting
confidence: 92%
“…In addition, the superior crystalline and surface morphology can further lead to large grain size. And it is well reported that larger the grain size, smaller is the band gap [23]. Hence, attributed to the superior crystalline and surface morphology achieved with the film prepared by PG, the film depicted smaller and superior band gap, in the present study.…”
Section: Pgsupporting
confidence: 62%
“…Figure 3 illustrates the Tauc's plot of thin film prepared using different solvents. However, the solvent variation doesn't affect much the optical properties of thin films as all films exhibited band gap in the range of 1.5-1.6eV, which is frequently reported [21][22][23]. 2 vs hʋ plot of thin film prepared using different solvents.…”
Section: Introductionmentioning
confidence: 73%
“…High equipment cost for large area deposition of thin films has made vacuum‐based approaches a poor choice. On the other hand, nonvacuum‐based fabrication methods such as chemical bath deposition, electrodeposition, spray pyrolysis, sol‐gel method, spin coating, dip coating, and SILAR have the advantage of economic and environmental cost.…”
Section: Introductionmentioning
confidence: 99%
“…Few reviews are available on this technique . A comprehensive review of the deposition of CZTS thin films through spray pyrolysis technique was not presented before.…”
Section: Introductionmentioning
confidence: 99%